1984
DOI: 10.1161/01.str.15.5.886
|View full text |Cite
|
Sign up to set email alerts
|

Disablement and quality of life after stroke.

Abstract: SUMMARY This study concerns the quality of life of patients after stroke and how this is influenced by disablement and emotional factors. Ninety-six consecutive patients of mean age 71 years were followed for two years. At the end of that time 23% had experienced a recurrence of stroke and 27% were deceased. Of the survivors 76% were independent as regards activities of daily life (ADL) and lived in their own homes. Age as well as initial function were prognostically important factors. Patients who could parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
164
1
19

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(200 citation statements)
references
References 15 publications
16
164
1
19
Order By: Relevance
“…Most studies have focused on selected components of QOL only, such as mental health or life satisfaction (Viitanen et al, 1988;Chi, 1995). Many studies have conceptualized QOL on the basis of theoretical assumptions or the researchers' own definitions and standards of what constitutes this construct (Ahlsio et al, 1984;Osberg et al, 1987;Pearlmann and Uhlmann, 1988b;Clark et al, 1997). By contrast, it has been suggested that an approach based on the exploration and validation of QOL from the perspective of the population being studied may provide more accurate information (Cohen, 1982;Maynard and Muth, 1987;McKenna, 1993).…”
Section: Qol Of Elderly Peoplementioning
confidence: 99%
“…Most studies have focused on selected components of QOL only, such as mental health or life satisfaction (Viitanen et al, 1988;Chi, 1995). Many studies have conceptualized QOL on the basis of theoretical assumptions or the researchers' own definitions and standards of what constitutes this construct (Ahlsio et al, 1984;Osberg et al, 1987;Pearlmann and Uhlmann, 1988b;Clark et al, 1997). By contrast, it has been suggested that an approach based on the exploration and validation of QOL from the perspective of the population being studied may provide more accurate information (Cohen, 1982;Maynard and Muth, 1987;McKenna, 1993).…”
Section: Qol Of Elderly Peoplementioning
confidence: 99%
“…Bu benzerlik üst ve alt ekstremite Brunnstrom evreleri arasın-da da görülmüştür. İnme sonrası dönemde yaşam kalitesini etkileyen faktörleri araştıran çalışmaların sonuçları ile uyumlu olarak İEÖ 3,0 için hastaların yaşam kalitelerinin motor gelişim ve fonksiyonellik düzeyi arttıkça olumlu yönde etkilendiği gözlenmiştir (33)(34)(35).…”
Section: Discussionunclassified
“…Kawachi & Malcolm (1989) assumed the quality of life to be 0.8 after stroke. Ahlsio et al (1984) assessed the quality of life after stroke for a two-year-period using a visual analog scale of I 00 mm and found that the quality of life decreased by approximately 20 mm. Wade & Hewer (1987) assessed the functional independence after stroke on a scale between 0-20 and the score was 16.9 6 months after the event, e.g.…”
Section: Quality Of Lifementioning
confidence: 99%